Comprehensive Analysis of Genes Associated With Sudden Infant Death Syndrome - Mehboob, Riffat; Kurdi, Maher; Ahmad, Mursleen; Gilani, Syed Amir; Khalid, Sidra; Nasief, Hisham; Mirdad, Abeer; Malibary, Husam; Hakamy, Sahar; Hassan, Amber; Alaifan, Meshari; Bamaga, Ahmed; et al. (Frontiers in Pediatrics, 2021)
Sudden infant death syndrome is a tragic incident which remains a mystery even after post-mortem investigation and thorough researches. This analysis is based on the genes reported in molecular autopsy studies conducted on SIDS so far. 20 original studies and 7 case reports were identified and included in this analysis. The genes identified in children or adults were not included. Most of the genes reported in these studies belonged to cardiac channel and cardiomyopathy genes. Cardiac channel genes in SIDS were scrutinized for further analysis. 42 unique genes were extracted after removing the common or repetitive genes. When the location of these genes was assessed, it was observed that most of these belong to Chromosomes 11, 1 and 3 in sequential manner. The pathway analysis shows that these genes are involved in regulation of heart rate, action potential, cardiac muscle cell contraction, heart contraction etc. The protein-protein interaction network was also very big and highly interactive. Most of these genes were regulated by histone modifications mainly H3K27me3 HeLa-S3 hg19 and H3K27me3 thymus mm9. SCN5A, CAV3, ALG10B, AKAP9 and many more were mainly found in these cases and were regulated by many transcription factors such as MYOG C2C1, CBX3 HCT11 etc. has-miR-133a-3p was found to be prevalent miRNA in the targeted genes. Molecular and computational approaches are a step forward towards exploration of these sad demises. It is so far a new arena but seems promising to dig out the root cause of SIDS in the years to come.